AN ANALYSIS OF MODAL AUXILIARIES FOUND IN CHARLES DICKENS’ OLIVER TWIST - Elsa Widya; Desmalia Purba (LPPM Universitas Darma Agung, 2021)
This research aims at finding out modal auxiliaries found in Charles Dickens’ Oliver Twist, their functions, and the most dominant modal auxilaries found there. This research was conducted by using qualitative method to analyze the data. The data were analyzed by applying some processes, they were: Identifying the data, Collecting the data from the novel, Analyzing and underlining the data related with the kinds and functions of modal auxiliaries. There are four modals that were analyzed based on their functions. Modal can can be used to show ability, possibility, permission and polite question. The function of possibility is dominantly used in Oliver Twist novel (40,96%). It is expected that the students of English Literature Department should have mastered the rules of the forms and functions of modal auxiliaries in writing their literary works because their literary works will be used by the language learners in their study, so they need to get the accepted materials, for example in this case, novel text.